Thermal behavior of irradiation-induced-deep level in bulk GaN used for fabricating blue light emitting diodes - Tran Thien, Duc; Le, Thi Hai Thanh (Communications in Physics, 2024)
Bulk GaN was irradiated by 2 MeV electron beam at a fluence of 5 × 1016 cm2 and studied by deep level transient spectroscopy (DLTS). After irradiation, a broad peak, including at least two traps, was detected. The trap D1 (EC – 0.16 eV) observed from a broad peak is induced during the annealing process below 550K and completely annealed out at 550K after 10 hours. The annealing process at 550K also forms a new trap D2 (EC – 0.25 eV). From the isothermal study the activation energy of the trap D2 in the annihilation process is obtained and has a value of 1.3 ± 0.3 eV. The pre-factor of the annihilation process suggested this process to be related to the free-carrier capture by multi-phonon emission. From the thermal behavior, the trap D2 was suggested to be related to gallium vacancy.